Body and Society: Symbolic Equation in Vampire Academy Series - Kustantinah, Indri; Pujiharto, Pujiharto; Rokhman, Muh Arif (Allure Journal, 2025)
The body serves as a symbol that describes the relationship between individual parts of an organism and the system as a whole. A structure of the social system of society can be found within the body. Literature works as the product of a culture and is considered a mirror of society. The body in literature is often a theme or symbol rich in meaning because the body can reflect various aspects of human life, such as identity, emotion, culture, politics, spirituality, and social relationships. The use of the body in literature often involves multidimensional exploration that inspires readers to understand the human experience more deeply. The Vampire Academy series brings about a body issue representing certain social structures of a society. This study aims to explore the symbols underlying the vampire body in the Vampire Academy series. The material and data were gained from library sources using a literary study method. The objects of this study are six novels by Richelle Mead from the Vampire Academy series, which tell the story of the lives of teenagers who fight against the class division structure in a school. The results include the body becoming a symbol of group identity, as seen in the tattoos of the Dhampir guardians’ class and the Human Alchemists, symbols of sexuality in body shape, and symbols of power in the blood, skin colour, and tooth shape.